Chasing Fire - Roberts, Nora; Lowman, Rebecca (Grand Haven, Mich. Brilliance Audio, 2011)
When a dark presence stalks female smoke-jumping firefighter Rowan Tripp in Montana, she wonders if she can get help from rookie smokejumper Gulliver Curry.
Unabridged
Compact discs.
Read by Rebecca Lowman.
Keywords: Women smokejumpers -- Fiction; Montana -- Fiction; Romantic suspense fiction; Audiobooks